Probe Cocktail to Assess Transporter Function in Sandwich-Cultured Human Hepatocytes - Cen Guo; Kenneth R. Brouwer; Paul W Stewart; Caroline Mosley; Kim L.R. Brouwer (Frontiers Media S.A., 2019)
PURPOSE: Probe substrates are used routinely to assess transporter function in vitro. Administration of multiple probe substrates together as a "cocktail" in sandwich-cultured human hepatocytes (SCHH) could increase the throughput of transporter function assessment in a physiologically-relevant in vitro system. This study was designed to compare transporter function between cocktail and single agent administration in SCHH. METHODS: Rosuvastatin, digoxin, and metformin were selected as probe substrates of hepatic transporters OATP1B1, OATP1B3, BCRP, P-gp, and OCT1. Total accumulation (Cells+Bile) and biliary excretion index (BEI) values derived from administration of the cocktail were compared to values obtained after administration of single agents in the absence and presence of a model inhibitor, erythromycin estolate. RESULTS: For rosuvastatin and metformin accumulation, the ratio of means [90% confidence interval (CI)] for cocktail to single agent administration was 100% [94%, 106%] and 90% [82%, 99%], respectively. Therefore, the cocktail and single-agent mode of administration were deemed equivalent per standard equivalence criterion of 80-120% for rosuvastatin and metformin accumulation, but not for digoxin accumulation (77% [62%, 92%]). The ratio of means [90% CI] for rosuvastatin BEI values between the two administration modes (105% [97%, 114%]) also was deemed equivalent. The ratio for digoxin BEI values between the two administration modes was 99% [78%, 120%]. In the presence of erythromycin estolate, the two administration modes were deemed equivalent for evaluation of rosuvastatin, digoxin, and metformin accumulation; the ratio of means [90% CI] was 104% [94%, 115%], 94% [82%, 105%], and 100% [88%, 111%], respectively. However, rosuvastatin and digoxin BEI values were low and quite variable in the presence of the inhibitor, so the BEI results were inconclusive. CONCLUSIONS: These data suggest that rosuvastatin and metformin can be administered as a cocktail to evaluate the function of OATP1B1, OATP1B3, BCRP, and OCT1 in SCHH, and that digoxin may not be an ideal component of such a cocktail.